Voxel-Based Morphometry of Cerebellar Lobules in Essential Tremor - Ågren, Richard; Awad, Amar; Blomstedt, Patric; Fytagoridis, Anders (Frontiers in Aging Neuroscience, 2021)
Background The extent of neurodegeneration underlying essential tremor (ET) remains a matter of debate. Despite structural magnetic resonance imaging (MRI) suggesting various extents of cerebellar atrophy, previous studies display substantial heterogeneity and include limited numbers of patients. Novel automated pipelines allow for detailed segmentation of cerebellar lobules based on structural MRI. Objective To compare volumes of cerebellar lobules of ET patients with healthy controls (HC) using an automated segmentation pipeline. Methods Structural MRI scans of deep brain stimulation eligible ET patients (n = 55) and of age- and gender-matched HC (n = 55; from the IXI database) were segmented using the automated CEREbellum Segmentation (CERES) pipeline. Lobule-specific volume differences between ET and HC were evaluated using a general linear model corrected for multiple testing. Results Total brain tissue volumes did not differ between ET and HC. On average, ET patients demonstrated reduced volumes of lobules I-II, left Crus II, left VIIB, and an increased volume of right X, as compared to HC. Conclusions A large cohort of ET patients demonstrated subtle signs of decreased cerebellar lobule volumes. The findings oppose the hypothesis of localized atrophy in cerebellar motor areas in ET, albeit not the possibility of cerebellar pathophysiology in ET. Prospective investigations using alternative neuroimaging modalities may further elucidate the pathophysiology of ET and provide insight into diagnostic and therapeutic approaches.